Assessment of microbiological growth on biometric devices - Mohd Nazri, Nur Nadrah Syamimi; Kalel Asmel, Nabel; Luiz Francisco Alves, José (Environmental and Toxicology Management, 2022)
Biometric devices are nowadays common in use for a variety of purposes. The current study aims to assess the bacteria growth on fingerprint scanners and morphological identification of the bacteria. The bacteria growth was determined through the colony forming units followed by morphological identification through hanging drop method and gram staining. The results showed the bacteria growth curve for dilution factor 10-6 showed the most accurate growth curve graph and was chosen for morphological identification. From morphological identification, the bacteria was observed for three days and from observation the bacteria’s growth moderately. Next, from gram staining method, the bacteria appeared reddish which mean its Gram-negative bacteria. Gram-negative bacteria are among the most significant public health problems in the world due to their high resistance to antibiotics so the recommendation is to change the use of biometric devices to more safe ways to avoid the spread of microorganisms in this pandemic era such as using online attendance system and using staff card. This study has been significant because it can confirm the existing of microorganisms on the surface of biometric devices as well as the types of the microbes by determining the bacteria growth and bacteria identification.